Saberes de professores da Educação Infantil sobre a BNCC: fontes, apropriações, implicações e desafios - Pimenta, Júlia Ines Pinheiro Bolota (2022)
The approval of the National Common Curricular Base (BNCC/2018) as an educational policy of a normative/prescriptive nature for basic education provoked the need to reflect on teaching activities, especially in early childhood education. This study investigated how early childhood education teachers appropriate the knowledge articulated by the educational policy - BNCC, highlighting what were the sources of knowledge of early childhood education teachers about this new policy, its appropriations and challenges. We sought to understand how its regulations and norms had repercussions on the professional knowledge of early childhood education teachers. The objective was to identify and describe the origins of teachers' knowledge about the BNCC, through attentive listening to these early childhood education professionals, according to their way of understanding this document. It also proposed to analyze how the teachers narrated the appropriation of this curricular policy, mapping the teaching knowledge used and their contribution to their development in the teachers' performance. Understanding how teachers appropriated the references articulated by educational policy helped to understand how these regulations impacted educational practices and the constitution of teaching knowledge, especially in early childhood education. The theoretical framework was based on two main pillars: the curricular issue, discussed and analyzed under the BNCC approach; and the training and knowledge of teachers seeking sources of information that build teaching knowledge, aiming at the early childhood education stage. The study was based on the concepts of curriculum presented by Gimeno Sacristán (1998, 2000) and Silva (2011), among others and, specifically on early childhood education, with the contributions of Kramer (1997, 2002, 2006), Barbosa and Horn (2008 ) and Oliveira (2010). Regarding the most relevant contributions regarding teaching knowledge, support was sought from Freire (1986), Tardif (2014), Tardif and Raymond (2000) in addition to Borges (2003, 2004). The used approach was qualitative and the questionnaires and interviews were the collection instruments used with the teachers in the perspective of narratives, to understand the attributed meaning on the impact caused by the homologation of the new educational policy. Bardin's Content Analysis (20016) was used as inspiration for data processing. Along the way, it was possible to perceive that the essential information about the BNCC was acquired in the educational context itself, in a fragmented way and according to the available information. With the outcome of the analysis, the results showed the great difficulty of the teachers in accessing information that could collaborate with the understanding of the determination, the importance of rescuing the knowledge of the experience and the expansion of knowledge caused by the change. In view of the constructed understandings, it is emphasized that policies developed at the central level, when only passed on to teachers and schools, destabilize teaching knowledge and the certainties produced by the knowledge of experience, throwing teachers into a “disorienting dilemma”, requiring reflection in training actions for its incorporation.